THE DETERMINANTS OF INTERNATIONAL TOURISM AND THE RESTRICTIONS TO THE INSERTION OF THE DEVELOPING COUNTRIES - A COMPARATIVE ANALYSIS IN SOUTH AMERICA, AFRICA AND SOUTH OF ASIA - Marcio José Vargas Cruz; Cássio Frederico Camargo Rolim (European Regional Science Association (ERSA), 2005)
This research had like general goal to identify the determinants of the international tourism flow, seeking diagnostic the main restrictions to the expansion of this sector in the countries in development, utilizing a comparative analysis for the regions of the South America, Africa and South of the Asia. To be specified the determinants of the international tourism flow, was applied the econometrics instrumental, aiming to establish its empirical evidence. In the analysis was utilized the panel model because it's shown adequate to the objective of identify the prominent factors of generalized form. Furthermore, this paper discuss the performance of the countries of the South America, Africa and South of Asia in the international tourism, with base in the determinant specified, seeking identify the empirical coherence of these general determinants in case of these countries and comparing the specificities and homogeneity between these regions, constituted by countries in development. The result of the study aims that the income is a fundamental determinant for explain the emission of tourists and there are indications of an elevated elasticity, what is translated in empirical coherence. Referring to the tourism attractive, we found the relevant paper of the risk related to the security and of the development of the country, identified through of the Human Development Index - HDI. The comparative analysis between the regions of the South America, Africa and South of the Asia, showed that the performance of these countries show consistency with the general determinants, in function of their conditions, for example, their geographic distance from the rich countries.
Keywords: 330